2019
DOI: 10.1038/s41598-019-49952-x
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphic variant rs1800734 influences methylation acquisition and allele-specific TFAP4 binding in the MLH1 promoter leading to differential mRNA expression

Abstract: Expression of the mismatch repair gene MutL homolog 1 (MLH1) is silenced in a clinically important subgroup of sporadic colorectal cancers. These cancers exhibit hypermutability with microsatellite instability (MSI) and differ from microsatellite-stable (MSS) colorectal cancers in both prognosis and response to therapies. Loss of MLH1 is usually due to epigenetic silencing with associated promoter methylation; coding somatic mutations rarely occur. Here we use the presence of a colorectal cancer (CRC) risk var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Interestingly, the rs1800734 G > A mutation disrupts the AP4 binding sequence, CAGCTG, located at the promoter of MLH1 . The loss of AP4 binding leads to an increase in DNA methylation at the promoter region and the epigenetic silencing of MLH1 [ 21 ]. In another study, Liu and colleagues found that the rs1800734 G > A mutation in several colorectal cancer cell lines enhances the long-range interactions between rs1800734 and the promoter and 3′ UTR region of the doublecortin-like kinase 3 gene ( DCLK3 ), resulting in an increase in the expression of this potential oncogene [ 22 ].…”
Section: Ap4 Dna Binding Sites As Targets For Snpsmentioning
confidence: 99%
“…Interestingly, the rs1800734 G > A mutation disrupts the AP4 binding sequence, CAGCTG, located at the promoter of MLH1 . The loss of AP4 binding leads to an increase in DNA methylation at the promoter region and the epigenetic silencing of MLH1 [ 21 ]. In another study, Liu and colleagues found that the rs1800734 G > A mutation in several colorectal cancer cell lines enhances the long-range interactions between rs1800734 and the promoter and 3′ UTR region of the doublecortin-like kinase 3 gene ( DCLK3 ), resulting in an increase in the expression of this potential oncogene [ 22 ].…”
Section: Ap4 Dna Binding Sites As Targets For Snpsmentioning
confidence: 99%
“…We carried out a meta-analysis and found no evidence of MSI EC risk association for rs1800734 (OR = 1.06 CI 0.85-1.33 p = 0.60) or any other SNPs in the MLH1 region (supplementary table 2), after correction for multiple testing. While the sample set is relatively small and the findings will need replicating, a similarly sized MSI CRC sample set gave a strong rs1800734 risk association (CRC MSI cases n = 170, controls n = 2686, OR = 1.95, 95% CI 1.50-2.55, p = 8.04 × 10 −7 , [16]). We estimate that we had 99% power to detect an OR of this magnitude for MSI EC.…”
Section: Resultsmentioning
confidence: 96%
“…In CRC tumour tissue stratified by genotype (but not in normal tissue), we previously found that rs1800734 acted as an MLH1 expression quantitative trait locus (eQTL) and a methylation quantitative trait locus meQTL (meQTL), with the risk allele associated with higher methylation and lower mRNA expression [16]. We were therefore interested to see whether this was true for EC tumours given that there was no association observed between rs1800734 and EC risk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations